The Effectiveness of Problem Based Learning Model with SMT Media Reviewed from Learning Results and Careful Attitude to Students' Materials of Multipling Class III - Desi Ambar Sari; Rusnilawati Rusnilawati (Budapest International Research and Critics University, 2022)
Mathematics as one of the subjects in school is considered to play an important role in education. Based on the Minister of National Education Regulation No. 20 of 2003 concerning the National Education System (National Education System) article 37 it is emphasized that,